VOLATILIZATION OF INORGANIC MERCURY BY ISOCHRYSIS GALBANA PARKE FROM AQUATIC SYSTEM - Alavandi, S V; Kaladharan, P; Pillai, V K (Indian Journal of Fisheries, 2011)
The loss of mercury added cxtraneously as an inorganic source to the algal cultures (Jsochrysis sp.) andto the seawatcr containing in situ phytoplankton populations off Cochin was determined quantitatively.Such loss of mercury was attributed to uptake as well as volatilisation of mercury (Hg") by the activityof phytoplankton and micro - organisms. The rate of removal of mercury in the culture system was 54%per day and that by in situ phytoplankton was 38%.